Full body musculoskeletal model for simulations of gait in persons with transtibial amputation. Issue 4 (12th March 2023) - Willson, Andrea M.; Anderson, Anthony J.; Richburg, Chris A.; Muir, Brittney C.; Czerniecki, Joseph; Steele, Katherine M.; Aubin, Patrick M.
Abstract: This paper describes the development, properties, and evaluation of a musculoskeletal model that reflects the anatomical and prosthetic properties of a transtibial amputee using OpenSim. Average passive prosthesis properties were used to develop CAD models of a socket, pylon, and foot to replace the lower leg. Additional degrees of freedom (DOF) were included in each joint of the prosthesis for potential use in a range of research areas, such as socket torque and socket pistoning. The ankle has three DOFs to provide further generality to the model. Seven transtibial amputee subjects were recruited for this study. 3 D motion capture, ground reaction force, and electromyographic (EMG) data were collected while participants wore their prescribed prosthesis, and then a passive prototype prosthesis instrumented with a 6-DOF load cell in series with the pylon. The model's estimates of the ankle, knee, and hip kinematics comparable to previous studies. The load cell provided an independent experimental measure of ankle joint torque, which was compared to inverse dynamics results from the model and showed a 7.7% mean absolute error. EMG data and muscle outputs from OpenSim's Static Optimization tool were qualitatively compared and showed reasonable agreement. Further improvements to the muscle characteristics or prosthesis-specific foot models may be necessary to better characterize individual amputee gait. The model is open-source and available at (https://simtk.org/projects/biartprosthesis ) for other researchers to use to advance our understanding and amputee gait and assist with the development of new lower limb prostheses.